UTILIZATION OF E COMMERCE IN EFFORTS TO INCREASE INCOME OF HOUSEWIVES - Meri Rahmania; Wati Wati; Yuli Diniah Zulbakri (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2021)
E-commerce is an abbreviation of electronic commerce which includes the process of buying and selling between sellers and buyers without having to have a physical store. With the existence of technology and information that is increasingly easily accessible via laptops, smart phones or other electronic devices, the online transaction process is easier and more attractive to the public many people. e-commerce can provide product sales solutions without being affected by regional boundaries. The ease of e-commerce that relies on technology and can send goods via expedition is very beneficial for both parties. International or cross-border business expansion can be realized thanks to this e-commerce. The goal to be achieved in carrying out this activity is to provide valuable insight and knowledge for housewives in an effort to increase their household income, by introducing E-commerce and how to use e-commerce to increase household income.Key words: E-Commerce, Housewife, Income